William Upham correspondence - Upham, William, 1792-1853.
ALS written by Upham to his wife describing the fire at the U.S. Capitol on that date and the destruction of the Library of Congress then housed there.
U.S. senator from Vermont and lawyer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Upham, William, -- Mrs., -- -1856 -- Correspondence; Library of Congress -- Fire, 1851.; United States Capitol (Washington, D.C.) -- Fire, 1851.; Lawyers; Senators, U.S. Congress -- Vermont